Pengembangan Aplikasi E-Commerce berbasis Android sebagai Sarana Jual Beli Barang Bekas menggunakan Metode Waterfall - Mayestika, Anastasia Kezia Beatrix; Sediyono, Eko (STIKOM Tunas Bangsa Pematangsiantar, 2023)
People often find it difficult to cope with the accumulation of household waste that includes furniture, clothes and other items. This accumulation of household waste does not only affect one house but also affects neighboring houses. Piles of unused items continue to accumulate in homes and other places, resulting in problems caused by inconvenience due to the large number of new items. With these problems, an application for buying and selling used goods was developed for people who want to sell or buy used goods. This research uses the Waterfall method as a software development method. This application is made by integrating the responsibilities of sellers and buyers simultaneously, resulting in one account that can buy and sell at the same time. With this application, it is hoped that the community can be helped in finding used products or goods that are still suitable for use.